Geographical ancestry affects normal hemoglobin values in high-altitude residents - Mairbäurl, Heimo; Gassmann, Max; Muckenthaler, Martina (Journal of applied physiology, 2020)
Increasing the hemoglobin (Hb) concentration is a major mechanism adjusting arterial oxygen content to decreased oxygen partial pressure of inspired air at high altitude. Approximately 5% of the world’s population living at altitudes higher than 1,500 m shows this adaptive mechanism. Notably, there is a wide variation in the extent of increase in Hb concentration among different populations. This short review summarizes available information on Hb concentrations of high-altitude residents living at comparable altitudes (3,500-4,500 m) in different regions of the world. An increased Hb concentration is found in all high-altitude populations. The highest mean Hb concentration was found in adult male Andean residents and in Han Chinese living at high altitude, whereas it was lowest in Ethiopians, Tibetans, and Sherpas. A lower plasma volume in Andean high-altitude natives may offer a partial explanation. Indeed, male Andean high-altitude natives have a lower plasma volume than Tibetans and Ethiopians. Moreover, Hb values were lower in adult, nonpregnant females than in males; differences between populations of different ancestry were less pronounced. Various genetic polymorphisms were detected in high-altitude residents thought to favor life in a hypoxic environment, some of which correlate with the relatively low Hb concentration in the Tibetans and Ethiopians, whereas differences in angiotensin-converting enzyme allele distribution may be related to elevated Hb in the Andeans. Taken together, these results indicate different sensitivity of oxygen dependent control of erythropoiesis or plasma volume among populations of different geographical ancestry, offering explanations for differences in the Hb concentration at high altitude.
Gesehen am 10.02.2021